Electrical and gas sensing properties of novel cobalt(II), copper(II), manganese(III) phthalocyanines carrying ethyl 7-oxy-4,8-dimethylcoumarin-3-propanoate moieties - (:unkn) unknown (WORLD SCI PUBL CO INC, 2018)
The synthesis of metallophthalocyanines (M = Co, Cu, Mn) bearing four ethyl 7-oxy-4,8-dimethylcoumarin- 3-propanoate moieties was performed. These novel compounds were characterized by elemental analysis, H-1-NMR spectroscopy, FT-IR, UV-vis and mass spectral data. DC and AC electrical properties of the films of metallophthalocyanines were investigated in the temperature range of 295-523 K. AC measurements were performed in the frequency range of 40-10(5) Hz. Activation energy values of the films took place between 0.55 eV-0.93 eV. Impedance spectroscopy measurements revealed that bulk resistance decreases with increasing temperature, indicating semiconductor properties. DC conductivity results also supported this result. Their gas sensing properties were also investigated for the vapors of Volatile Organic Compounds (VOCs), n-butyl acetate (200-3200 ppm) and ammonia (7000-56000 ppm) between temperatures 25-100 degrees C. Sensitivity and response times of the films for the tested vapors were reported. The results were found to be reversible and sensitive to the vapors of n-butyl acetate and ammonia. It was found that Mn(OAc) Pc showed better sensitivity than CoPc and CuPc for n-butyl acetate vapors at all measured vapor concentrations and temperatures. Mn(OAc) Pc also showed better sensitivity than CoPc and CuPc for ammonia vapors at 22 degrees C.
Keywords: coumarin; metallophthalocyanine; VOC; gas sensing; conductivity; impedance spectra; SUBSTITUTED METAL-FREE; ELECTROCHEMICAL PROPERTIES; PHOTOCHEMICAL PROPERTIES; CHEMICAL SENSORS; THIN-FILMS; COUMARIN; COMPLEXES; TETRA; SEMICONDUCTORS; CONDUCTION